Recognizing Child Abuse in Radiology - Oestreich, Alan E.; Caré, Marguerite M. (Springer International Publishing : Imprint: Springer, 2017)
This book is both a personal review of experience in the diagnosis of child abuse and its differential diagnosis, intended to instruct beginners, and a reliable source of information for the more experienced health care provider. Emphasis is placed on normal findings that simulate abuse, true and false diagnoses of metabolic bone disease as the cause of fractures, abusive head trauma, and the problem of zealous abuse-denying "experts." Plain radiography is emphasized, with appropriate mention of, ultrasound, CT, MRI, - in detecting childhood abuse is clearly explained, and individual chapters focus on neuroradiological evaluation and the radiological assessment of abdominal, thoracic, and subcutaneous abnormalities. Guidance is provided on how to exclude a range of alternative diagnoses, on the documentation of concerns over potential abuse, and on the needs of the clinician in relation to the radiologist. Recognizing Child Abuse in Radiology will be of value for radiologists in training and practice, for health care workers, and for other interested professionals.